The Impact of Thin Capitalisation Rules on Corporate Tax Burden: Evidence from the Emerging Market - Loso Judijanto (Nomico, 2025)
This study examines the impact of thin capitalization rules on corporate tax burdens in emerging markets, focusing on firm-level behavioural responses and policy effectiveness in Indonesia and Malaysia. Using a panel dataset of 78 firm-year observations drawn from 2015 to 2022, the study applies fixed-effects and random-effects regression models to assess changes in leverage, interest expenses, effective tax rates, and book tax differences following the implementation of thin capitalization rules. The findings indicate that the regulations significantly reduce corporate leverage and related-party interest expenses, consequently increasing cash effective tax rates among heavily leveraged firms. The results further show that firms engage in substitution toward non-debt tax planning channels when interest deductions are restricted, highlighting behavioural adaptability in response to regulatory pressure. Differences in regulatory effectiveness between Indonesia and Malaysia underscore the importance of enforcement capacity and administrative consistency in shaping compliance outcomes. The study concludes that thin capitalization rules contribute meaningfully to reducing debt-based profit shifting but require complementary tax governance reforms to maximize their impact. The results provide empirical insights relevant for policymakers seeking to strengthen corporate tax bases in emerging markets.